Importance of Pd monomer pairs in enhancing the oxygen reduction reaction activity of the AuPd(100) surface: A first principles study - Ham, Hyung Chul; Hwang, Gyeong S.; Han, Jonghee; Yoon, Sung Pil; Nam, Suk Woo; Lim, Tae Hoon (ELSEVIER SCIENCE BV, 2016)
Based on density functional theory calculations, we present that pairs of 1st nearest Pd monomers play an important role in significantly enhancing the oxygen reduction reaction (ORR) on the AuPd(100) surface. While the catalytic ORR activity tends to be sensitive to the surface atomic ordering, we find that the Pd monomer pairs lead to a substantial reduction in the activation barrier for O/OH hydrogenation with no significant suppression of O-O bond scission, thereby considerably lowering the overall activation energy for the ORR as compared to the case of pure Pd(100). On the other hand, an isolated Pd monomer tends to greatly suppress the O-O bond cleavage reaction, which in turn slows down the ORR kinetics. Unlike the monodentate adsorption of O-2 on an isolated Pd monomer, the pairing of Pd monomers allows O-2 adsorption in a bidentate configuration and consequently facilitating O-O bond scission. However, the barrier for OH hydrogenation at each Pd site shows no significant change between the isolated and paired cases, while it is noticeably lower than the pure Pd case. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: DENSITY-FUNCTIONAL THEORY; HYDROGEN-PEROXIDE; ATOMIC ARRANGEMENTS; ADSORPTION; ENSEMBLES; ALLOYS; H-2; CHEMISORPTION; CLUSTERS; PD(111)